Penggunaan Media Video Animasi Untuk Meningkatkan Hasil Belajar IPA Pada Kelas IX A di SMP Negeri 1 Balaesang - Aulia, Azni; Lilies; Febriani, Vita Indri; Febriawan, Aan; Rafiqah; Jamhari, Mohammad (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This research aims to improve student learning outcomes in Biology subjects through the use of animated video media in improving science learning outcomes of grade IX A students at SMP Negeri 1 Balaesang. The method used is this research is a Classroom Action Research (PTK) design with four stages, namely planning, implementation, teacher observation, and student observation. The research subjects amounted to 28 students. The data collection instruments in this study used teacher observation sheets, student observation sheets, and posttests. The research will be conducted in July 2025. Based on the results of the study, it shows that the use of animated video media in science subjects has proven to significantly improve student learning outcomes. This is aimed at the results of data analysis that has been carried out in the implementation of the Iyang cycle, showing that the level of student learning outcomes of learning completeness reached 67%, while in cycle II it increased to 100%. In addition, students’ responses to learning using animation media were very positive. Thus, it can be concluded that animated video media is effective in helping to understand science material and increasing student involvement in the learning process.